Participation in social/lifestyle activities in people with multiple sclerosis: Changes across 10 years and predictors of sustained participation. (November 2020) - Johansson, Sverker; Ytterberg, Charlotte; Gottberg, Kristina; Holmqvist, Lotta Widén; von Koch, Lena; Conradsson, David
Background: Identification of people with multiple sclerosis (PwMS) with increased risk of restricted participation in social and lifestyle activities (e.g. social outings and pursuing a hobby) could guide the development of interventions supporting sustained participation. Objective: To explore changes in participation in complex and social everyday activities over 10 years in PwMS in relation to multiple sclerosis (MS) severity and to identify predictors of sustained participation. Methods: This study was based on a 10-year follow-up of 264 PwMS living in Stockholm County, Sweden. Ten-year changes in participation in social/lifestyle activities were assessed and compared between PwMS with different MS severity with the Frenchay Activities Index using age- and sex-related normative values. Multiple logistic regression analyses were used to predict sustained participation at 10 years using personal factors, disease severity and functioning as independent variables. Results: While a majority of people with mild MS demonstrated sustained participation (67%), a minority of PwMS moderately (26%) and severely affected by MS (5%) demonstrated sustained participation. Significant predictors of sustained participation after 10 years were walking speed ⩾1.2 m/s and ⩾32 correct responses on the Symbol Digit Modalities Test. Conclusion: Our findings accentuate the importance for health services to support mobility and cognition to obtain sustained participation.